Etnična kultura Slovencev v osebnem arhivskem fonda Izmaila Ivanoviča Sreznjevskega (na podlagi gradiva iz leta 1841) - Kerimova, Marijam M. (Etnolog. Nova vrsta (Ljubljana), 2023)
The article is based on rare archival material held in the Russian State Archive of Literature and Art (RGALI, Moscow), and focuses on field ethnographic material collected by I.I. Sreznevsky during his scientific trip to Slovenia in 1841. Sreznevsky – who was a well-known Russian Slavist with a wide range of interests, a great expert on the history and philology of the southern and western Slavs, professor at the University of Kharkov and later at the University of St Petersburg – recorded in his travel diaries linguistic differences and dialects of the Slovene language, along with the customs, rituals, everyday family life, elements of the material culture and beliefs of the local populations.
Keywords: arhivsko gradivo; I. I. Sreznjevski; Rusija; Slovenci; vsakdanje življenje